2023
DOI: 10.1002/adma.202307186
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic‐Assembled Covalent Organic Frameworks@Ti3C2Tx MXene Vertical Fibers for High‐Performance Electrochemical Supercapacitors

Xiaolin Zhu,
Yang Zhang,
Zengming Man
et al.

Abstract: The delicate design of innovative and sophisticated fibers with vertical porous skeleton and eminent electrochemical activity to generate directional ionic pathways and good faradic charge accessibility is pivotal but challenging for realizing high‐performance fiber‐shaped supercapacitors (FSCs). Here, we develop hierarchically ordered hybrid fiber combined vertical‐aligned and conductive Ti3C2Tx MXene (VA‐Ti3C2Tx) with interstratified electroactive covalent organic frameworks LZU1 (COF‐LZU1) by one‐step micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The CV curves display regular rectangular shapes with broad humps (Figure a and Figure S7), indicating the high ionic conductivity of Ni 3 (HITP) 2 -PP-EA. The double layer capacitance was calculated to be 176.3 F·g –1 at a scan rate of 10 mV·s –1 (Figure b), which is near four times higher than that of PP-EA (48.3 F·g –1 ) and comparable with other supercapacitors reported previously. , Besides, no shape deformation was observed during the electrochemical measurements, indicating the excellent stability of the actuators, which is crucial for long-term operation. The Nyquist plot of the low-frequency region of Ni 3 (HITP) 2 -PP-EA is almost vertical to the y- axis (Figure c), indicating an ideal capacitance behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The CV curves display regular rectangular shapes with broad humps (Figure a and Figure S7), indicating the high ionic conductivity of Ni 3 (HITP) 2 -PP-EA. The double layer capacitance was calculated to be 176.3 F·g –1 at a scan rate of 10 mV·s –1 (Figure b), which is near four times higher than that of PP-EA (48.3 F·g –1 ) and comparable with other supercapacitors reported previously. , Besides, no shape deformation was observed during the electrochemical measurements, indicating the excellent stability of the actuators, which is crucial for long-term operation. The Nyquist plot of the low-frequency region of Ni 3 (HITP) 2 -PP-EA is almost vertical to the y- axis (Figure c), indicating an ideal capacitance behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have devised a solution to this problem by creating hybrid fibers with a predetermined hierarchy through a microfluidic synthesis process. These fibers combine vertically aligned and conductive Ti 3 C 2 T x MXene (VA-Ti 3 C 2 T x ) with interstratified electroactive COFs (covalent organic frameworks), LZU1 (COF-LZU1) . The generated VA-Ti 3 C 2 T x @COF-LZU1 fibers showcase an impressive gravimetric capacitance of 787 F g –1 when assessed in a three-electrode setup.…”
Section: Cutting-edge Applicationsmentioning
confidence: 99%
“…Each material has its advantages and disadvantages, which can be efficiently harnessed and minimized through the creation of a ternary composite. Numerous researchers have reported that integrating multiple materials with varied textures and charge storage mechanisms improves the overall capacitive behavior, ultimately leading to enhanced supercapacitive performance. …”
Section: Introductionmentioning
confidence: 99%